The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5657/fas.2013.0243
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Gene Flow Patterns in Pollicipes mitella in Korea Inferred from Mitochondrial DNA Sequence Analysis

Abstract: Genetic diversity and gene flow patterns in Pollicipes mitella were investigated with a nucleotide sequence analysis of 514 base pairs from the mitochondrial cytochrome c oxidase subunit I gene (COI) in 124 samples collected from six Korean populations. In total, 59 haplotypes were defined by 40 variable nucleotide sites in the COI region. The haplotypes had shallow haplotype genealogy and no geographic associations. All populations had high haplotype diversity (0.909 to 0.979) and low nucleotide diversity (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…Although elasmobranch fish are highly mobile when adults (Gaither, Bowen, Rocha, & Briggs, ), thermal barriers (such as the Tsushima Warm Current) may preclude contemporary gene flow between the mottled skate populations in the East Sea and Yellow Sea. Similar examples of species affected by the biogeographic barrier between the East and Yellow Seas have been reported, including Hemigrapsus sanguineus (Hong et al., ), Pollicipes mitella (Yoon, Jung, & Kim, ), Konosirus punctatus (Myoung & Kim, , ), and Ammodytes personatus (Kim, Lee, Lee, Kim, & Kim, ).…”
Section: Discussionsupporting
confidence: 63%
“…Although elasmobranch fish are highly mobile when adults (Gaither, Bowen, Rocha, & Briggs, ), thermal barriers (such as the Tsushima Warm Current) may preclude contemporary gene flow between the mottled skate populations in the East Sea and Yellow Sea. Similar examples of species affected by the biogeographic barrier between the East and Yellow Seas have been reported, including Hemigrapsus sanguineus (Hong et al., ), Pollicipes mitella (Yoon, Jung, & Kim, ), Konosirus punctatus (Myoung & Kim, , ), and Ammodytes personatus (Kim, Lee, Lee, Kim, & Kim, ).…”
Section: Discussionsupporting
confidence: 63%
“…The results indicate that the C. mitella in Fujian province has a medium to high level of genetic diversity, with a low nucleotide diversity. This is comparable to the findings in other invertebrates, such as Portunus trituberculatus (h=0.582, π=0.00158) (Liu et al, 2009), but higher than those observed in China (h=0.490, π=0.00158), and lower than the Korean population (h=0.909, π=0.00550) (Yoon et al, 2013). The results of this study suggest that the C. mitella in Fujian province experienced a rapid population expansion from an ancestral population with a small effective size.…”
Section: Discussionsupporting
confidence: 87%
“…The results indicate that the C. mitella in Fujian province has a medium to high level of genetic diversity, with a low nucleotide diversity. This is comparable to the findings in other invertebrates, such as Portunus trituberculatus (h=0.582, π=0.00158) (Liu et al, 2009), but higher than those observed in China (h=0.490, π=0.00158), and lower than the Korean population (h=0.909, π=0.00550) (Yoon et al, 2013). The results of this study suggest that the C. mitella in Fujian province experienced a rapid population expansion from an ancestral population with a small effective size.…”
Section: Discussionsupporting
confidence: 84%